Guidelines far dealing wi th female victimes of family violence - Deza Villanueva, Sabina (2012)
This article makes sorne suggestions for operators care of family violence on how to provide quality service to women affected by this problem. Also it provides a set of guidelines to prevent revictimization by professionals that address this form of violence. The text requires a number of considerations to facilitate expression of the needs and expectations ofhelp from women against violence. tapies covered are: Features and reactions of women affected by family violence. Reasons why women do not talk about family violence affects them, and Guidelines for quality care